Moderasi Beragama: Kajian Analisis Deskriptif Perspektif Heterogenitas di Indonesia - Pribadi, Redho Slamet (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes that the Indonesian nation is a multicultural society with its pluralistic nature. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. In such a multicultural society, tensions and conflicts often occur between cultural groups and have an impact on the harmony of life. The purpose of this writing is to discuss the cultural diversity of the Indonesian nation, religious moderation in diversity and the role of religious instructors in realizing the peace of the Indonesian people. The method used is library research. The conclusion of this study is that in the life of a heterogeneous Indonesian society, multicultural understanding and awareness is needed that respects differences, pluralism and a willingness to interact fairly with anyone. An attitude of religious moderation is needed in the form of acknowledging the existence of other parties, having a tolerant attitude, respecting differences of opinion and not imposing their will by means of violence. The role of the government, community leaders and religious instructors is needed to socialize and develop religious moderation to the community for the sake of harmony and peace. Keywords: Religion Moderation; Perspective; Heterogeneity